The power of helicopter money revisited: A new Keynesian perspective - Thomas J. Carter; Rhys R. Mendes (Bank of Canada, 2020)
We analyze money financing of fiscal transfers (helicopter money) in two simple New Keynesian models: a "textbook" model in which all money is non-interest-bearing (e.g., all money is currency), and a more realistic model with interest-bearing reserves. In the textbook model with only non-interest-bearing money, we find the following: A money-financed fiscal expansion can be more stimulative than a debt-financed fiscal expansion of equal magnitude. However, the extra stimulus requires that the central bank abandon its usual feedback rule for an extended period, allowing interest rates to instead be determined by the rate of money creation. Moreover, the extra stimulus associated with money financing stems solely from its implications for the path of short-term interest rates and cannot be attributed to an oft-cited Ricardian-equivalence argument that money financing avoids the adverse wealth effects associated with higher taxes under debt financing. Because the stimulative effects of money financing are driven by its implications for interest rates, a combination of debt financing and sufficiently accommodative forward guidance can replicate all welfare-relevant outcomes while bypassing the potential political-economic complications associated with helicopter money. Apart from these complications, money financing also has the drawback that it would allow money-demand shocks to generate volatility in output and inflation, much as was the case under the money-targeting regimes of the 1970s and 1980s. In the model with interest-bearing reserves, we find the following: The rate of money creation determines the interest rate on reserves, but broader interest rates are invariant across debt- and money-financing regimes. As a result, money financing delivers no extra stimulus relative to debt financing. Overall, results suggest that helicopter money cannot be justified on the grounds that it would allow policy-makers to get more stimulus out of a given fiscal expansion: either money financing has no extra stimulative benefits to offer, or all potential benefits could be pursued more effectively and robustly using alternative policies.
Keywords: E12; E41; E43; E51; E52; E58; E61; E63; 330; Credibility; Economic models; Fiscal policy; Inflation targets; Interest rates; Monetary policy; Monetary policy framework; Transmission of monetary policy; Uncertainty and monetary policy